Effect of 5.31Ti (at.%) content used as ternary in quaternary Cu-rich high-temperature shape memory alloy cast via arc melting - Basbag, Gunes; Karaduman, Oktay; Canbay, Canan Aksu; Ozkul, Iskender; Boyrazli, Mustafa (Redakcia Kovove Materialy, 2023)
In this work, the new quaternary CuAlTiMg high-temperature shape memory alloy (HTSMA) with an unprecedented composition and with extended solubility of Ti was produced by the arc melting method. The thermal shape memory effect characterization tests were done by performing a series of differential calorimetric (DSC and DTA) measurements. The obtained thermograms of the alloy displayed the martensitic phase transformation peaks. The forward (martensite to austenite) phase transformation was found to occur at above 350 degrees C, which qualifies the produced alloy as an HTSMA. The microstructural XRD measurement was performed to reveal the atomic planes of martensite structures formed in the alloy, which constitute the shape memory effect property of the fabricated alloy. The alloy surface was monitored by optical microscopy image taken at room temperature, and finely dispersed Ti-rich X-phases were observed.
Keywords: CuAlTiMg high-temperature shape memory alloy (HTSMA); shape memory effect; martensitic transformation; differential scanning calorimetry (DSC); differential thermal analysis (DTA); arc melting